Antifungal potential of Clove essential oil (Syzigium aromaticum L.) in the post-smoking preservation of mackerel (Trachurus trachurus) in Benin - DEGNON, GNIMABOU RENÉ; ADJOU, EULOGE SÈNAN; NOUDOGBESSI, JEAN PIERRE AKODOGBO; DAHOUENON-AHOUSSI, Edwige; SOUMANOU, MANSOUROU MOHAMED; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2013)
The present work aims to study the effectiveness of essential oil of Syzygium aromaticum (L.) in the post-smoking preservation of mackerel (Trachurus trachurus) in Benin. A total of sixty-seven (67) processors selected on smoking zone of Djidje (South of Benin) were surveyed. This survey was coupled with the sampling of smoked fish. Microbiological analyses were performed to identify potential sources of microbial contamination and investigate the bioactivity potential of essential oil extracted from leaves of Syzygium aromaticum as antifungal agent in the post-smoking preservation of mackerel (Trachurus trachurus). Results obtained showed that smoked fishes collected are contaminated by microorganisms, such as coliforms, Staphylococcus spp, yeasts and molds. Results of in vitro antifungal tests revealed that the essential oil has strong antifungal activity with the Minimum Inhibitory Concentrations (MIC) of 10 µl/ml against fungi strains isolated from smoked fishes. Results of microbial count on smoked fish preserved with essential oil of S. aromaticum indicated that after five days of storage, no visible growth of bacteria and fungi was detected in samples of smoked fish preserved by adding the essential oil using adjunction method in all essential oil concentrations (0.25, 0.5 and 1ml/70g) tested. However, with the injection method, only the essential oil concentration of 1ml/70g has totally inhibited the bacteria and fungi growth. In opposition, major signs of tampering were noted in control smoked fish after 5 days. The preservation of smoked fish by incorporation essential oil increased the shelf life of the product. However, this protection is not for a long time due to the volatile property of the essential oil.
Keywords: Smoked fish; Trachurus trachurus; microbiological quality; essential oils.